2016
DOI: 10.1186/s13568-016-0236-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipid production through simultaneous utilization of glucose, xylose, and l-arabinose by Pseudozyma hubeiensis: a comparative screening study

Abstract: Co-fermentation of glucose, xylose and l-arabinose from lignocellulosic biomass by an oleaginous yeast is anticipated as a method for biodiesel production. However, most yeasts ferment glucose first before consuming pentoses, due to glucose repression. This preferential utilization results in delayed fermentation time and lower productivity. Therefore, co-fermentation of lignocellulosic sugars could achieve cost-effective conversion of lignocellulosic biomass to microbial lipid. Comprehensive screening of olea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 40 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, some strains can consume more than two sugars simultaneously. For instance, strains of Rhodosporidium and Pseudozyma show a simultaneous consumption of glucose, xylose and fructose [115] and glucose, xylose and arabinose, respectively [116]. Likewise, Rhodosporidium kratochvilovae and Y. lipolytica showed a simultaneous consumption of different pentoses and hexoses on mixed sugar media [117,118].…”
Section: Sugar Conversion Into Sco and Regulatory Mechanisms In Sugarmentioning
confidence: 99%
“…Furthermore, some strains can consume more than two sugars simultaneously. For instance, strains of Rhodosporidium and Pseudozyma show a simultaneous consumption of glucose, xylose and fructose [115] and glucose, xylose and arabinose, respectively [116]. Likewise, Rhodosporidium kratochvilovae and Y. lipolytica showed a simultaneous consumption of different pentoses and hexoses on mixed sugar media [117,118].…”
Section: Sugar Conversion Into Sco and Regulatory Mechanisms In Sugarmentioning
confidence: 99%
“…Simultaneous mixed-sugar utilization was achieved, which was attributed to mild glucose repression in conjunction with strong carbon catabolite activation for growth on xylose and cellobiose. In another exhaustive screening of 1,189 yeast isolates, Tanimura et al demonstrated P. hubeiensis IPM1-10 was able to co-utilize glucose, xylose, and arabinose in the artificial hydrolysate and accumulated high amounts of lipid (Tanimura et al, 2016). These findings suggest the importance of broadening the current collection of microbial species for efficient fermentation of multiple sugars in biomass hydrolysates.…”
Section: Native Xylose-utilizing Yeastsmentioning
confidence: 99%
“…[26][27][28] Exhaustive screening of large number of yeast isolates led to the discovery of Pseudozyma hubeiensis IPM1-10 that converts sugar mixtures consisting of glucose, xylose and arabinose to lipids. 29 Oleaginous microbes utilise xylose exclusively by phosphoketolase pathway resulting in lower yields of lipids. 30 Due to the absence of glucose repression in P. hubeiensis, this yeast will turn out to be a potential candidate for second generation biodiesel production from hydrolysate of cellulosic biomass.…”
Section: Enzymes and Lipids Produced By Pseudozyma Hubeiensismentioning
confidence: 99%